Financiamento iternacional de ONGs LGBTI no Brasil: estratégias e desafios - Silva, Pedro Henrique Lopes (2022)
In recent decades, transnational support from entities such as private foundations and multinational companies allowed LGBTI organizations in Brazil to gain access to new sources of funds. Dialoguing with the findings in the literature that reveal inequalities in access to these resources and their ability to induce changes in the management of organizations, this article aims to identify, through the case study method, the challenges and strategies of two NGOs with projects focused on LGBTI populations in Brazil for international fundraising. It was identified that the strategies used by the organizations revealed inequalities in the access to these resources, in particular due to the requirements of the international grants that make the participation of smaller organizations unfeasible. Finally, despite the differences in the choice of financing method, both shared challenges related to the volatility in the volume of these resources